2022
DOI: 10.1016/j.jviromet.2021.114411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two RT-PCR techniques for SARS-CoV-2 RNA detection in serum for microbiological diagnosis

Abstract: Presence of SARS-CoV-2 RNA in serum (viremia) of COVID-19 patients has been related to poor prognosis and death. The aim of this study was to evaluate both the ability to detect viremia in COVID-19 patients of two commercial reverse real-time-PCR (rRT-PCR) tests, Cobas® and TaqPath™, comparing them with a gold standard method, and their implementation in microbiology laboratories. This retrospective cohort study included 303 adult patients (203 diagnosed with COVID-19 and 100 non-COVID-19 patients) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…At the Department of Microbiology at the Karolinska University Hospital, Huddinge, Stockholm, the following commercial techniques approved for diagnosing SARS-CoV-2 were used: cobas SARS-CoV-2 assay (Roche, Pleasanton, California), targeting the Envelope (E) and Open Reading Frame (ORF) 1 gene [ 19 ] or NeuMoDx SARS-CoV-2 assay (NeuMoDx, Ann Arbor, Michigan) targeting non-structural protein 2 (Nsp 2 ), RNA-dependent RNA polymerase ( RdRp ) and nucleocapsid (N) genes. In addition, a validated in-house method targeting the RdRp and E-genes was utilised.…”
Section: Methodsmentioning
confidence: 99%
“…At the Department of Microbiology at the Karolinska University Hospital, Huddinge, Stockholm, the following commercial techniques approved for diagnosing SARS-CoV-2 were used: cobas SARS-CoV-2 assay (Roche, Pleasanton, California), targeting the Envelope (E) and Open Reading Frame (ORF) 1 gene [ 19 ] or NeuMoDx SARS-CoV-2 assay (NeuMoDx, Ann Arbor, Michigan) targeting non-structural protein 2 (Nsp 2 ), RNA-dependent RNA polymerase ( RdRp ) and nucleocapsid (N) genes. In addition, a validated in-house method targeting the RdRp and E-genes was utilised.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was estimated in 49 patients to validate the primary objective of the study “SARS-CoV-2 viremia as a biomarker of disease severity” (ongoing manuscript) based on the results of our previous retrospective studies ( 10 , 15 ); nevertheless, 57 patients were finally included.…”
Section: Methodsmentioning
confidence: 99%
“…Ramírez AM et al [96] reported a sensitivity, specificity, PPV, NPV, and kappa coefficient of 73.63%, 97.6%, 96.73%, 75%, and 0.69, respectively. The details are provided in Table 3.…”
Section: Serum Samplesmentioning
confidence: 99%